Influence of Sustainability of Spiritual-Economic Projects on Growth of Methodist Church in Kaaga Synod, Kenya - Lairangi, Jeniffer Kinya; Kinoti, Mary; Njoroge, John (International Journal of Professional Practice, 2024)
The mission of the church is to contribute to the transformation of the dehumanizing economic structures. Nevertheless, churches in Kenya have experienced a lack in financial leadership and spiritual support for projects; occasioned by absence of spiritual guidance in the implementation of economic projects. The purpose of this study was to investigate the influence of sustainability of spiritual-economic projects on growth of the Methodist church in Kenya, Kaaga Synod. The study was guided by stewardship theory, and adopted descriptive research design. The target population was 25 Circuits of Methodist Church, Kaaga Synod, Meru, Kenya. Purposive sampling technique was used to select 53 project managers, while simple random sampling technique was used to select 196 project members, constituting 30 percent of the project membership population across the sampled circuits. Questionnaires were used to collect data. A pre-test study was conducted in Methodist church in Nairobi synod, where 5 projects heads and 20 community project members were included. The data was analyzed using descriptive statistics such as mean, frequencies and percentage. SPSS version 29 was used to analyze the data, and results were presented in tables. The study found out that church projects, such as schools and financial institutions, were negatively impacted by Covid-19, resulting in low income. Consequently, the church has taken longer time than anticipated to deliver its mandate. The study recommends that the church council to develop strategies that would enable the church projects recover more quickly from the adverse effects of Covid-19 pandemic.